LANDSCAPE BIODIVERSITY CHANGES IN FOREST VEGETATION AND THE CASE STUDY OF THE LAVAZ - INGEGNOLI, V.; GIGLIO, E: (Annali di Botanica, 2008)
The Italian CONECOFOR programme of forest monitoring inserted in 2004 the study of “landscape biodiversity” because a forest is not only an ecosystem, it is –first of all- a landscape. The Biological Integrated School of Landscape Ecology, widening the concept of landscape, is able to elaborate a new methodology of vegetation survey (LaBISV) based on ecological parameters. This methodology allows to study the changes in forest vegetation referred both to landscape structure and function and landscape biodiversity. As an example of application here is presented in extreme synthesis the case study of the landscape unit of the Lavazé Pass (Trentino- Alto Adige). Traditional methods of forest evaluation did not find any ecological problem in the landscape forest of Lavazé. On the contrary, it was possible to demonstrate that this forest landscape unit was altered in few years (1998-2004) because of the tourist pressure and ski rides.